Service Quality Factors Influencing the Use of Artificial Intelligent Security Technology in UAE - Alafreet Alkuwaiti, Salem Ahmed Abdulla; Ahmad, Ahmad Nur Aizat; Abo Mosali, Najmaddin (International Journal of Sustainable Construction Engineering and Technology, 2023)
This study assessed various factors related to service quality in influencing artificial intelligence security technology. It was carried out through quantitative approach where the data of respondents perceptions of UAE citizens towards the enhancing service quality in the UAE's AI security sector was derived through queationnaire survey. The factors were categorized in four groups which are performance expectancy group with seven factors;  effort expectancy group with seven factors; social influence group with four factors; and facilitates condition group with five factors. With these factors, the respondents were requested to gauge the degree of influence of each factor using 5-points likert scale. The questionnaire survey managed to secure 359 completed questionnaire forms. The data from these forms were analysed using descriptive statistic. It was found that facilitates condition group of factor is the most influencing category on service quality to adopt AI technology. It can be concluded that the overall results indicate that facilitates condition, effort expectancy and performance expectancy groups are reported having very high influencing categories while social influence group having high influencing ategory. It was also found that AI technologies are very frequently used technologies by the UAE citizens. Based on the study, it is deduced that service quality is a basic consideration as reported by the UAE personnel for adoption of any technology.